“Pura vida”: A Costa Rican Cultural Expression from a Foreigner’s Perspective - Smith, Andrew (Revista de Lenguas Modernas, 2018)
This paper will examine the Costa Rican expression “pura vida”. This expression, which has come to represent Costa Rica itself, is literallyseen and heard everywhere in the country. Even though a superficialinterpretation of these two words may be as simple as “hello,” “good-bye,” “thank you” or “you’re welcome,” a close study of how the expression is used reveals that it is far more elaborate and complex than it appears. It is quite possible that not even Costa Ricans genuinely understand all the potential meanings that the expression “pura vida” embraces.